Consumer Trust To Online Shop Seller Reputation (Quantitative Research about Relationship of Consumer trust to Online Shop Seller Reputation in Social Media at Economy Management Student of UMS 2012th Generation) - Budi Indrawati, Dwi; , Nur Latifah Umi Satiti, MA; , Rinasari Kusuma, M.I.Kom (2016)
The trust is an attitude or behavior is consumers who grow in taking decisions. The trust is formed when a seller and buyer, is engaged in a process of effective communication, so that the seller can influence a consumer to buy the product on sale. a good reputation will increase consumer confidence towards products marketed online. The purpose of this research is to know consumer trust relationship of consumer trust to online shop seller reputation in social media at Economy Management Student of UMS 2012th Generation. This research is quantitative with survey method. The sample of this research is 81 student of Economy Management Student UMS 2012th generation, and use data correlation analysis. Based on analysis result with use SPSS, is known correlation calculation result with use correlation product moment technique, be found 0,753. Then that result compared with product moment with respondents or N=81, in significant level 5% be found value 0,220, so the result of correlations research found correlation level and the strenght correlation between consumer trust to onlie shop seller reputation, is have strenght correlation.